Prototyping in Software Quality Assurance: A Survey With Software Practitioners - Macedo, Gretchen Torres De; Fontão, Awdren de Lima; Gadelha, Bruno Freitas (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2022)
User Interface Prototyping is a resource for exploring and communicating ideas, which is largely used in software development in activities like requirements elicitation or product discovery. Existing works indicate that the use of prototyping can be related to the improvement of software quality. Therefore, we conducted a survey with practitioners from the software industry to investigate how prototyping has been used in quality assurance activities. As a result, we identified different development process models that adopt prototyping to support various activities, such as the identification of new technologies to be adopted, the definition of user stories, planning activities, identification of business rules and navigation flows, front-end and back-end implementation, reviews, and tests. However, we also identified prototyping-related problems, such as teams from the same company using prototyping in a non-standard way, or the use of outdated prototypes during tests, approval, and training phases. In this way, we verified that the adoption of prototyping as a tool to support the software development process must follow usage rules explicitly defined in the development process and clearly communicated to developers, so they can positively influence the improvement of the quality of software.